Cancer in Europe: Death sentence or life sentence?. (September 2016) - Liu, Lifang; O'Donnell, Peter; Sullivan, Richard; Katalinic, Alexander; Moser, Elizabeth Charlotte; de Boer, Angela; Meunier, Françoise; ,
Abstract: With so many adults and children receiving successful treatment for their cancer, survivorship is now a 'new' and critical issue. It is increasingly recognised that the growing numbers of survivors face new challenges in their bid to return to 'normal' life. What is not yet so widely recognised is the need for a broad response to help them cope—with stigmatisation, misunderstanding, lifelong issues of confidence and social adaptation, and even access to employment and to financial services. As a further stage in its programme of attention to this aspect of cancer, the European Organisation for Research and Treatment of Cancer (EORTC) brought survivors, researchers, carers, authorities and policymakers together at a meeting in Brussels in March/April 2016, to learn at first hand about the posttreatment experience of cancer survivors. The meeting demonstrated that while research is well advanced in many of the medical consequences of survivorship, understanding is still lacking of many non-clinical, personal and administrative issues. The meeting raised the discussion of survivorship research beyond the individual to a population-based approach, exploring the related socioeconomic issues. Its exploration of initiatives across Europe countries provoked new thinking on the need for effective collaboration, with a new focus on non-clinical issues, including effective dialogue with financial service providers and employers, improvements in collecting, exchanging and accessing data, and above all, ways of translating research outcomes into action. This will require wider recognition that, as Françoise Meunier, Director Special Projects, EORTC, said, 'It is time for a new mind set'. Highlights: Survivorship, an issue for individuals and society. Survivorship poses significant economic challenges for many former patients and their families. Prioritise research on social challenges facing cancer survivors. Join forces and integrate data and expertise in research in Europe. Encourage survivor-centred, multistakeholder, sustainable communication platform.